ANALYSIS OF THE INFLUENCE OF THE CAPITAL STRUCTURE OF THE COMPANY : THE COMPANY’S GROWTH AND PROFITABILITY AS A MODERATING VARIABLE (EMPIRICAL STUDY OF CORPORATE PROPERTY AND REAL ESTATE IN BEI 2010-2014) - Patricia Martha Lena; Amries Rusli Tanjung; Yesi Mutia Basri (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2017)
This is research aims to examine the effect of capital structure on corporate valuewith profitability and growth of the company as a moderating variable. The data used in this research is secondary derived from the financial statements of companies listed on the Indonesia Stock Exchange in 2010-2014. By using purposive sampling, this study got 30 sample companies. The analytical method used in this research was moderated regression analysis (MRA). The results showed that the positive effect on the capital structure of the company's value. Profitability could strengthen the influence of capital structure on firm value Positive. Growth companies can strengthen the influence of capital structure to the company's value in a negative way.